Analisis Motivasi Muzakki Dalam Keputusan Mengeluarkan Zakat - Fahrul Shafi’, Muhammad; Cahyadi, Nur; Harianto, Prayudi (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
Zakat in Islam states that there are several rights of other people, especially the rights of the poor towards people who have excess wealth. The assets you own will be more blessed if some of them can be distributed using zakat. This will certainly be very helpful in alleviating poverty. Muzakki who have a very good understanding of zakat will influence the muzakki's interest in zakat to be high and vice versa. Awareness is the state of being sensitive or aware of a topic or subject. The muzakki's motivation, understanding and awareness in the decision to issue zakat are related to each other because if the muzakki does not have understanding and awareness then there will be no motivation within the muzakki to issue zakat. Likewise, if ordinary people do not have an understanding and awareness about zakat, they will not be motivated to pay zakat.